PENGARUH PENGANGGARAN PARTISIPATIF PADA BUDGETARY SLACK DENGAN KOMITMEN ORGANISASI, INTERNAL LOCUS OF CONTROL DAN KETIDAKPASTIAN LINGKUNGAN SEBAGAI VARIABEL PEMODERASI - Pratini, I Gusti Ayu Asti; Budiartha, I Ketut; Astika, Ida Bagus Putra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.09.TAHUN 2016, 2016)
This study aims to identify and obtain empirical evidence of moderation of organizational commitment, internal locus of control and uncertainty of the environment against the effects of participatory budgeting in the budgetary slack. Collecting data using primary data collected using questionnaire techniques. The total sample of 232 echelons of sectors in the Bali Provincial Government selected based method of proportionate stratified random side. Data analysis technique used is moderation regression analysis (MRA). The results obtained are the result of a test of organizational commitment indicates that there is moderation organizational commitment and weaken the influence of participatory budgeting in the budgetary slack, there is a moderation of internal locus of control and weaken the influence of participatory budgeting in the budgetary slack and there is a moderation of the uncertainty of the environment and strengthening the influence of participatory budgeting on budgetary slack.
Keywords: budgetary slack, participatory budgeting, organizational commitment, internal locus of control, environmental uncertainty